Implementation of an Annual Goal´s Plan for the improvement of scientific production in a Colombian university. Positives and negatives aspects - Vázquez-Miraz, Pedro; Posada Llorente, Marcos Ricardo (Revista General de Información y Documentación, 2020)
We present in the following investigation, a detailed descriptive analysis of the high-impact scientific production (defined this as all research indexed in the Scopus) database of a Colombian private university, the Universidad Tecnológica de Bolívar, during the period between 2017 – 2019. The purpose of this paper is to clarify the positives and negatives aspects of the implementation of an Annual Goal´s Plan, related to the scientific production of the teaching staff of this University during the first year of validity (2019). For it, it was reviewed the information of the Scopus database according with several variables such as the kind of product, number of authors, thematic area… and its temporal evolution in these three years, also making a comparison with the rest of universities of its closest environment. Although, the institution was able to overcome by far the goal set (surpass a hundred products), the allocation of scientific production quotas for teachers deepened other trends already present in this university, such as the extreme dependence on work of certain Engineering departments, and the preference for publishing conference proceedings instead of books, book’s chapters or journals.